When sustainable may not mean just: a critical interpretation of urban water consumption decline in Barcelona. Issue 5 (4th May 2017) - March, Hug; Sauri, David
ABSTRACT: In this paper, we document and analyse the recent decline (2007–2013) in domestic water consumption in Barcelona. The postulates of ecological modernisation and market environmentalism celebrate these declines as an example of sustainable development, thanks to the combination of more efficient technologies and economic incentives. However, these interpretations ignore the new framework of social relations introduced by technologies and markets and take environmental improvements as homogeneous and universal regardless of distributional issues. Therefore, it would be perfectly possible to achieve optimal environmental situations in the context of deteriorating social conditions, particularly in terms of access to basic resources by the most disadvantaged. We explored the relationships between declining domestic water consumption and the uneven impact of the economic crisis on Barcelona's urban geography. We found that the alleged increase in environmental sustainability that follows decline in resource use translates into highly uneven social impacts in terms of both accessibility and consumption. These results show that water flows have profound political dimensions and that water justice in terms of distributional costs and benefits but also in terms of recognition and participation of the less well-off should be a fundamental component of future urban water policies in this area.